VERDICT ON IMPLEMENTATION OF THE FORMULATION GRACE PERIOD LEGISLATION BY THE CONSTITUTIONAL COURT - Nur Fadilah; Devanda Dian Kusuma (International Journal of Law and Legal Ethics, 2020)
This study is initiated by many decisions of the Constitutional Court that are not implemented, even though the nature of the decisions of the Constitutional Court is final and binding. The type of research used is normative legal research. This study is descriptive. The type of data used is secondary data. Secondary data collection techniques were obtained through literature review. The primary and secondary data were analyzed qualitatively. The results of the study show that first, the Constitutional Court Decision is not implementative when the decision does not include a grace period for its implementation, whereas the Constitutional Court Decision which includes a grace period is followed up very quickly by the legislators. Second, the model of the Constitutional Court Decision which is executable in the future is the Constitutional Court Decision which includes a grace period and institutionalization of constitutional question through the addition of the authority of the Constitutional Court.